Complete mitochondrial genome of freshwater goby Rhinogobius shennongensis (Perciformes, Gobiidae): genome characterization and phylogenetic analysis - Xiao Jiang Chen; Lin Song; Xing Peng Han; Quan Wang (Mitochondrial DNA. Part B. Resources)
In this study, we present the complete mitochondrial genome of Rhinogobius shennongensis, sequenced using the Illumina HiSeq platform. The result is a circular mitogenome of 16,500 base pairs (bp) with a pronounced A + T nucleotide bias. Phylogenetic analysis was conducted using both Bayesian inference (BI) and maximum-likelihood (ML) methods, utilizing the complete mitochondrial genomes of R. shennongensis and 19 additional Rhinogobius species. The analysis indicated a close mitochondrial relationship between R. maculagenys and R. shennongensis. This research not only enriches genetic resources but also supports phylogenetic studies within the genus Rhinogobius. To further clarify evolutionary dynamics, additional mitochondrial genome sequencing of other Rhinogobius species is essential.